Apoio e sustentação ao desamparo materno: uma escuta psicanalítica - Prata, Alcimeri Kühl Amaral Veiga (2016)
he aim of this study was to analyze four cases of women who became mothers for the first time and were answered through an empathetic psychoanalytic listening, directed to the issue of maternal helplessness. The theoretical framework focused on the contributions of Freud, Klein, Bion and Winnicott, among other psychoanalysts who specifically work with motherhood. One of the most relevant results was the construction of a listening model psychoanalytically oriented towards motherhood vicissitudes